Bone wax in the treatment of partial epiphysiodesis of distal femoral growth plate: Case report at 10-year follow-up - Basiglini, Luca; Aulisa, Angelo Gabriele; Bandinelli, Diletta; Toniolo, Renato Maria; Falciglia, Francesco (Frontiers in Surgery, 2022)
The growth plate is the weakest structure in the skeleton of a child and a frequent site of injury or fracture; physeal injuries represent 15%–30% of all fractures in children. Of all growth plate fractures, the incidence of growth arrest and disorders is around 15%. Here, we discuss a female patient who, at the age of 5 years, was treated for a polytrauma that involved a complex lesion of the growth plates of the knee. Four days after trauma, she underwent closed reduction surgery and internal fixation with cannulated screws for femoral and tibial fractures of the growth plate. A 20° valgus deviation of the left knee was found at 3-month postoperative clinical check-up likely as a result of a growth disorder of the femur. She was diagnosed with valgus knee secondary to epiphysiodesis of the lateral portion of the femoral physis and she was readmitted to the hospital. In the operating theater, an open femoral de-epiphysiodesis was performed with a burr; the drilled hole was then filled with bone wax. At 20-month post-trauma follow-up, the left knee was still valgus about 20° relative to the other side. During follow-up, a slow but progressive improvement in the axis of the lower limbs was noted. Clinical and radiographic control 10 years after the trauma showed a complete recovery of the axis of the lower limbs. In the initial stages, the presence of bone wax in the area of de-epiphysiodesis allowed for stabilization of the deformity on the 20° of preoperative valgus. The interpretation of the growth cartilage activity occurred in an asymmetrical way such as to realign the femoral load axis, it can be based on the different mechanical stimulus on the two knee areas due to the preexisting deformity. There is no unanimous evidence in the literature in terms of management of growth disorders resulting from this type of injury. Bone wax resulted in effectively filling the hole of de-epiphysiodesis in the distal femoral growth plate and allowed us to obtain the response of the growth plate and to improve the recovery time in young children.